Design of a Sugar Cane Juice Extracting Machine. - Mubangizi, Elias (Kabale University, 2025)
Basically, the essence of this report is to design and develop a machine from available resources capable of extracting juice from sugar canes, specifically for local farmers. The sugar cane juice extracting machine is constructed to assist these farmers and juice vendors in extracting juice after harvesting following challenges they face negatively impact sugarcane juice vendors, profitability, poor quality juice, increased labor costs, and slow production rates. Use of hands and manual machines to extract juice. The machine is designed to use electricity as a source of power to the AC motor which provides rotational speed to the roller shaft through the pulley and belt system. This system plays two important roles. One is to transmit torque from the motor to the shaft and the second one is to reduce speed. It acts as a speed-reducer mechanism instead of using a gearbox. This is achieved by connecting a pulley of a small diameter on the motor shaft and a bigger pulley to the roller shaft with the use of a belt. The machine consists of various components like the hopper, which receives the sugarcane, the crushing roller which crushes the sugarcane a motor that provides power, and the frame to provide support to the entire assembly. The general objective of the study was; to develop an easy, and effective sugar cane juice-extracting machine. The methods included library search, field surveys, internet search, and interviews. Reviewing design parameters of different scholars to come up with the conceptual design and developing the layout by use of SOLID WORKS. The design for different major components was carried out while others were just selected. Stress analysis and simulations were also performed to study the behavior of the shaft.